2019
DOI: 10.5935/0004-2749.20190020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact lenses on ocular biometric measurements based on swept-source optical coherence tomography

Abstract: To determine the reliability of sweptsource optical coherence tomography in cases in which soft contact lenses cannot be removed when acquiring biometric measurements. Methods: Eight subjects were included and only one eye per participant was analyzed. Each eye was measured six times by swept-source optical coherence tomography with the IOLMaster 700 instrument (Carl Zeiss Meditec, Jena, Germany). Axial length, central corneal thickness, anterior chamber depth, lens thickness, and keratometric measurements wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…Therefore, the results of these devices cannot be compared to each other. The results of this study disagree with those found by Ferrer-Blasco et al [12], whose study showed a significant increase in CCT, but also in ACD and AL when comparing naked eye measurements versus CL wearing. Changes in these parameters were directly correlated with the CL thickness.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of these devices cannot be compared to each other. The results of this study disagree with those found by Ferrer-Blasco et al [12], whose study showed a significant increase in CCT, but also in ACD and AL when comparing naked eye measurements versus CL wearing. Changes in these parameters were directly correlated with the CL thickness.…”
Section: Discussioncontrasting
confidence: 99%
“…The inclusion criteria were as follows: auto refracted sphere of -8.00 to +4.00 D, astigmatism of ≤ 3.00 D, and/or K values of 41 to 47 D [11]. The exclusion criteria were as follows: presence of ocular or systemic disorders that could affect the measurements, closed-angle glaucoma, history of ocular surgery and/or history of hypersensitivity to anaesthesia [12].…”
Section: Participantsmentioning
confidence: 99%
“…Participants were only included if their refractive spherical error was between +2.00 and -4.00D, their refractive cylindrical refractive that was less than 1.00D, their Best Corrected Visual Acuity (BCVA) was higher than 1.0 in a Snellen Chart [6,7] and their score on a Low Vision Quality of Life (LVQOL) [8] higher than 50 points (LVQOL ± SD = 56.6 ± 2.50 points). Participants were excluded if they had a history of conjunctival, scleral, or corneal disease, glaucoma, a history of ocular surgery and/or, diabetes mellitus, thyroid disorders, and/or systemic disorders that could affect the measurements [9]. No participant was under any type of topical and systemic medications or used artificial tears at the time of the study.…”
Section: Sample and Inclusion Criteriamentioning
confidence: 99%
“…Yet, the correlation between ocular biometric parameters and concomitant exotropia remains unclear, and few studies have evaluated the ocular biometric parameters in concomitant exotropia. Ocular biometric measurements have been widely used in clinical practices such as the calculation of intraocular lens (IOL) power (19), candidate screening for refractive surgery, monitoring of the ametropic progression (20), estimation of the ocular mechanical properties (21), measurement of ocular anatomic changes on different accommodative stimuli (22,23), or wearing contact lenses (24). As a novel non-contact and highresolution optical biometric device, OA-2000 (Tomey, Nagoya, Japan) incorporates swept-source optical coherence tomography and a Placido-disc topographer, which could automatically find a measurable point and complete the scans quickly and accurately.…”
Section: Introductionmentioning
confidence: 99%